Lack of evidence for the involvement of Merkel cell polyomavirus in pulmonary Langerhans cell histiocytosis. Issue 2 (11th May 2020) - Jouenne, Fanélie; Le Goff, Jérôme; Bugnet, Emmanuelle; Salmona, Maud; Meignin, Véronique; Lorillon, Gwenaël; Sadoux, Aurélie; Cherot, Janine; Lebbé, Céleste; Mourah, Samia; Tazi, Abdellatif
Langerhans cell histiocytosis (LCH) is currently considered a rare neoplastic disease with an inflammatory component, driven by genomic alterations in the mitogen-activating protein kinase (MAPK) pathway, including BRAF V600E, MAP2K1 mutations and BRAF deletions [1, 2]. Lung involvement is frequently observed in adult LCH patients, almost exclusively in young smokers of both sexes [3]. The aetiology of LCH, including pulmonary LCH (PLCH), remains unknown. A viral triggering factor of LCH has long been suspected, but the results of studies are inconclusive [4, 5]. Compared to control lung tissues from smokers, MCPyV DNA is rarely detected in PLCH lesions and is not associated with alterations of the MAPK pathway. A viral trigger in PLCH pathogenesis remains elusive. https://bit.ly/2xKmkIo